AN INVESTIGATING OF YEMEN EFL LEARNERS’ WRITING PROBLEMS - Al-Marrani, Yahya Mohammed (Institut Agama Islam Negeri (IAIN) Bone, 2023)
This study attempts to investigate the writing problems encountered by Yemeni EFL learners. The sample of the study comprised 70 undergraduate students from Sana’a University. The data were collected using a questionnaire to identify Yemeni EFL Learners’ Writing Problems. The results of the study indicated that students have some crucial problems when writing a paragraph or an essay. The results showed that the participants faced difficulty in planning or outlining the points before writing a paragraph or an essay. Furthermore, they faced difficulties in developing a good topic sentence for a paragraph and a thesis statement for an essay, writing supporting sentences to support the topic sentence, organizing ideas together in a unified and coherent manner, and writing a concluding sentence/concluding paragraph that summarizes the points of a paragraph or an essay. The study proposed some recommendations and suggestions to help Yemeni EFL learners to overcome their writing problems.